Additional Coiling of Previously Coiled Cerebral Aneurysms: Clinical and Angiographic Results - Slob, Marjan J.; Sluzewski, Menno; van Rooij, Willem Jan; Roks, Gerwin; Rinkel, Gabriël J. E. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Some cerebral aneurysms that have been coiled reopen over time and additional treatment should be considered to reduce the risk of recurrent hemorrhage. Our purpose was to assess procedural complications and angiographic results of additional coiling in patients with previously coiled but reopened aneurysms and to evaluate protection against (re)bleeding.METHODS: We compared procedural complications of initial coiling of 488 aneurysms in 439 patients with those of 53 additional coiling procedures in 41 reopened aneurysms in 40 patients. Angiographic results of additional coiling were assessed. We compared episodes of (re)bleeding in patients with complete or near-complete aneurysm occlusion after additional coiling with those of patients with incomplete aneurysm occlusion at 6-month follow-up angiography who were not additionally treated or who still had incomplete occlusion after additional coiling.RESULTS: Thirty-five procedural complications occurred in 488 initial coiling procedures, and no complications occurred in 53 additional procedures. Complete or near-complete angiographic occlusion after additional coiling was obtained in 31 (76%) of 41 aneurysms. Rebleeding occurred in two of 29 patients with incomplete aneurysm occlusion but in none of the 31 patients with complete or near-complete occlusion after additional coiling.CONCLUSION: Additional coiling of previously coiled aneurysms has a low procedural complication rate and leads to sufficient occlusion in most aneurysms. The data indicate that successful additional coiling decreases the risk of rebleeding.